Legal Protection for Owner Fishermen and Cultivating Fishermen in Fishery Product Sharing Agreements (Study of the Fisherman Community of Malabero Village, Bengkulu City) - Radbiah Rahmadani; Hendi Sastra Putra; Sandi Aprianto (JURNAL HUKUM SEHASEN, 2022)
Indonesia as an archipelagic country, the existence of fish resources contained in Indonesian waters is quite large, both in terms of quality and various types that can be managed and utilized for the benefit of the nation and state, especially society as a whole. Based on Law Number 16 of 1964 concerning the System for Production Sharing Patterns, cultivator fishermen in marine fisheries will get a share of 75% of the net output if a sailboat is used and 40% if a motor boat is used. This study aims to determine the form of fishery production sharing agreements between owner fishermen and working fishermen in the Malabero fishing community in Bengkulu City, to find out how the profit sharing system is implemented by the Malabero fishing community in Bengkulu City, and to find out how legal protection is for owner fishermen and fishermen. cultivators in a fishery production sharing system. The research method used is empirical and normative. The empirical approach is research conducted by analyzing problems by combining legal materials which are a group of secondary data and combined with primary data obtained in the field. The practice of profit sharing that occurs in the fishing community of Malabero village, Bengkulu City has occurred based on local customs or has been passed down from generation to generation and is a local wisdom carried out by pledging a profit sharing agreement in the form of speech / oral without any written evidence and only attended by a few witnesses Usually, the fishery product sharing carried out by the fishing community of Malabero village, Bengkulu City, the owner fisherman will get a share of 50% of the net result and the cultivator fishermen will get a share of 10% of the net result after the ship departure costs are issued. This explanation is based on fishing gear in the form of net, while fishing gear in the form of owner's trawl will get 50% share and cultivator fishermen will get a share of 25% of the net proceeds after the ship departure costs are incurred. Therefore, it is necessary to have a form of fishery production sharing agreement between owner fishermen and cultivator fishermen which is more legally proven, and there is a need for regulations that can protect fishermen in terms of fishery production sharing patterns, especially for small (traditional) fishermen.